Penerapan Konseling Kelompok Berbasis Falsafah Siri'na Pacce dalam Upaya Meningkatkan Self-Esteem Siswa - Wahyuni, Sri; Saman, Abdul; Yasser, Ahmad (Guidance : Jurnal Bimbingan dan Konseling, 2023)
The purpose of this study is, 1. To determine the description of self-esteem before and after the implementation of group counseling based on the philosophy of siri’ na pacce, 2. To determine the implementation of group counseling based on the philosophy of siri’ na pacce, 3. To determine the effect of group counseling based on the philosophy of siri’ na pacce in increasing student’s self-esteem at SMP IT Anugrah Hidayah Makassar. This research used true xperimental with pre-test post-test design. The population in this study amounted to 20 people and the sample 16 people used the proportionate stratified random sampling method. The result of the data analysis test show 1. The level of self-esteem before being given treatment is in the low category and after being given treatment the level of student’s self-esteem increase, 2. The implementation of these services includes the planning, design, implementation and evaluation stages, 3.after being given treatment in the form ogf group counseling based on the philoophy of siri’ na pacce, it is found that student’s self-esteem incerased.